2021
DOI: 10.1021/acsanm.1c01818
|View full text |Cite
|
Sign up to set email alerts
|

Triple Narrowband Mid-Infrared Thermal Emitter Based on a Au Grating-Assisted Nanoscale Germanium/Titanium Dioxide Distributed Bragg Reflector: Implications for Molecular Sensing

Abstract: Mid-infrared (MIR) light sources with selective multiple narrowband and minimal angular dependence have desired properties for practical sensing applications. In this work, a triple narrowband MIR thermal emitter is realized by a hybrid structure composed of gold (Au) gratings on top of an alternate stacking germanium/titanium dioxide (Ge/TiO 2 )-distributed Bragg reflector (DBR) and a Au reflector. Upon transverse-electric (TE)-polarized light illumination, three types of resonant modes including the hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Even though a variety of mid-IR emitters are now available (e.g., silicon photonic devices ( CMOS Emerging Technologies, 2012 ), cascade lasers (quantum and inter-band) ( Jung et al., 2017 ), non-cascade-based lasers, chalcogenide fiber-based photonic devices ( Sincore et al., 2018 ), suspended-core tellurium-based chalcogenide fiber photonic devices ( Wu et al., 2018 ), and infrared thermal emitters ( Hsiao et al., 2021 ), these emitters are not as cost-effective as MIRGA, and also have not been tested in a domestic setting or with foods.…”
Section: Resultsmentioning
confidence: 99%
“…Even though a variety of mid-IR emitters are now available (e.g., silicon photonic devices ( CMOS Emerging Technologies, 2012 ), cascade lasers (quantum and inter-band) ( Jung et al., 2017 ), non-cascade-based lasers, chalcogenide fiber-based photonic devices ( Sincore et al., 2018 ), suspended-core tellurium-based chalcogenide fiber photonic devices ( Wu et al., 2018 ), and infrared thermal emitters ( Hsiao et al., 2021 ), these emitters are not as cost-effective as MIRGA, and also have not been tested in a domestic setting or with foods.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that gratings can be stacked on top of DBR to enhance the polarization-correlation emission rate, selective resonance and high radiation directional property [33,36]. Figure 7 shows a diagrammatic drawing of the photonic Tamm structure, which is composed of a one-dimensional (1D) periodic SiC grating deposited onto a ZnSe/Ge-based DBR (consisting of 5 pairs of ZnSe/Ge alternances with λ/4 layer thickness and center wavelength λ Bragg = 12 µm) with an additional Ge spacer layer.…”
Section: Selective Resonance Response With Sic Gratingsmentioning
confidence: 99%
“…TPPs are considered as practical substitutes for traditional surface plasmons due to lower dielectric loss, longer propagation distance, and higher field strength . These capabilities qualify such structures to be used in fluorescence control, , sensors, , absorbers, , low-threshold lasing, narrow-band thermal emitters, , and so forth.…”
Section: Introductionmentioning
confidence: 99%